Dolegliwości bólowe kręgosłupa wśród personelu pielęgniarskiego = Spinal pain among nurses - Baumgart, Mariusz; Radzimińska, Agnieszka; Szpinda, Michał; Kurzyński, Paweł; Goch, Aleksander; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Baumgart Mariusz, Radzimińska Agnieszka, Szpinda Michał, Kurzyński Paweł, Goch Aleksander, Zukow Walery. Dolegliwości bólowe kręgosłupa wśród personelu pielęgniarskiego = Spinal pain among nurses. Journal of Education, Health and Sport. 2015;5(9):633-646. ISSN 2391-8306. DOI10.5281/zenodo.31730 http://dx.doi.org/10.5281/zenodo.31730 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A633-646 https://pbn.nauka.gov.pl/works/640916 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. Dolegliwości bólowe kręgosłupa wśród personelu pielęgniarskiego Spinal pain among nurses Mariusz Baumgart1, Agnieszka Radzimińska2, Michał Szpinda1, Paweł Kurzyński3, Aleksander Goch2, Walery Zukow4 1. Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra i Zakład Anatomii Prawidłowej, Bydgoszcz, Polska / Nicolaus Copernicus University in Toruń, Collegium Medicum in Bydgoszcz, Department of Anatomy, Poland 2. Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska / Nicolaus Copernicus University in Toruń, Collegium Medicum in Bydgoszcz, Department of Physiotherapy, Poland 3. Student kierunku Fizjoterapia Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Bydgoszcz, Polska / Physiotherapy student, Nicolaus Copernicus University in Toruń, Collegium Medicum in Bydgoszcz, Poland 4. Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska / Kazimierz Wielki University, Bydgoszcz, Poland Autor do korespondencji: baumgartmar@gmail.com - Mariusz Baumgart, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra i Zakład Anatomii Prawidłowej, ul. Łukasiewicza 1, 85-821 Bydgoszcz, Polska Słowa kluczowe: bóle kręgosłupa, pielęgniarki, kwestionariusz ODI, kwestionariusz NDI. Key words: back pain, nurses, Oswestry Disability Index, Neck Disability Index. Streszczenie Wstęp Badania epidemiologiczne pokazują, że częstość występowania bólu kręgosłupa wśród personelu pielęgniarskiego waha się w granicach 75% dla odcinka lędźwiowego kręgosłupa, natomiast dla odcinka szyjnego w granicach 60%. Niepokojący jest fakt, że liczba ta ciągle rośnie. Materiał i Metody Badaniem objęto 60 losowo wybranych pielęgniarek pracujących na różnych oddziałach szpitalnych w regionie kujawsko-pomorskim. W celu oceny niepełnosprawności spowodowanej bólem kręgosłupa lędźwiowego i szyjnego zastosowano polską wersję Oswestry Disability Scale (ODI) i Neck Disability Index (NDI). Wyniki Ocena stopnia niepełnosprawności za pomocą kwestionariusza ODI i NDI pozwoliła zakwalifikować badaną grupę do przedziału wskazującego na umiarkowaną niepełnosprawność. Masa ciała oceniana wskaźnikiem BMI miała wpływ na nasilenie dolegliwości bólowych kręgosłupa w badanej grupie. Dolegliwości bólowe kręgosłupa w badanej grupie dotyczą osób o krótkim stażu pracy i zwiększają się odpowiednio u osób ze stażem dłuższym. Wnioski Dolegliwości bólowe kręgosłupa w grupie zawodowej pielęgniarek stanowią poważny problem medyczny i społeczny. Istnieje potrzeba wprowadzenia w tej grupie zawodowej programów profilaktycznych ukierunkowanych na prewencję dysfunkcji kręgosłupa. Summary Introduction Epidemiological research shows that frequency of the pain in the spine in nursing staff occurs approximately in 75% for the lumbar vertebrae and in 60% for the cervical vertebrae. Unfortunately these numbers are still growing. Material and Methods The study included 60 randomly selected nurses working in different wards of the region kujawsko-pomorskie. To assess disability due to pain of the lumbar and cervical spine used Polish version of the Oswestry Low Back Pain Disability Scale (ODI) and Neck Disability Index (NDI). Results The assessment of the disability level for the people being examined with the ODI and NDI questionnaires allowed to qualify the examined group to the moderate level of disability. The weight estimated with the BMI indicator had an impact on the increase of the pain in the spine among the examined group. The pain in the spine refers to people with short length of service and it increases among those with longer length of service. Conclusions Pain in the spine among nurses is a serious medical and social problem. There is a need to implement preventive programs for this professional group aiming at spine dysfunctions prevention.